Proteomic profiling of maize opaque endosperm mutants reveals selective accumulation of lysine-enriched proteins - Morton, Kyla J (Journal of experimental botany, 2016)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology.